Efektifitas Penggunaan Dana Desa Dalam Rangka Meningkatkan Kesejahteraan Masyrakat di Desa Sungai Batang Kecamatan Martapura Barat Kabupaten Banjar - Putera, Muhammad Irfan Maulana; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of this study is to determine the effectiveness of the use of village funds in order to improve the welfare of the community in Sungai Batang Villages. In this research using qualitative descriptive method. The type of data used in the form of secondary data about the development of effectiveness of the use of Village funds in order to improve the welfare of the community in Sungai Batang Villages. The results of research can be used by local governments to set policies on the use of Village Funds in order to increase the welfare of the community in Sungai Batang Villages. Based ont the results of this study, effectiveness of the use of Village Funds in order to improve the welfare of the community in Sungai Batang Villages is goes according to plan and manages to achieve village targets and development that comes from Village Fund programs in accordance with community expectations also what the community needs according to the results of village development.